Diversity and Dynamics of Salmonella enterica in Water Sources, Poultry Litters, and Field Soils Amended With Poultry Litter in a Major Agricultural Area of Virginia - Gu, Ganyu; Strawn, Laura K.; Zheng, Jie; Reed, Elizabeth A.; Rideout, Steven L. (Frontiers in Microbiology, 2019)
The Eastern Shore of Virginia (ESV) is a major agricultural region in Virginia and in the past has been linked to some tomato-associated outbreaks of salmonellosis. In this study, water samples were collected weekly from irrigation ponds and wells in four representative vegetable farms (Farms A-D, each farm paired with one pond and one well) and a creek as well. In addition, water samples from two sites in the Chesapeake Bay on the ESV were collected monthly. Poultry litter was sampled monthly from three commercial broiler farms. Soil samples were collected monthly after fertilization with poultry litter from 10 farms in 2014, and another 14 farms in 2015. A most probable number method was used to detect Salmonella enterica presence and concentration in collected samples. Presumptive Salmonella colonies were confirmed by the cross-streaking method. Molecular serotyping was carried out to determine the Salmonella serovars. The average prevalence of Salmonella in pond, well, creek, and bay water samples were 19.3, 3.3, 24.2, and 29.2%, respectively. There were significant spatial and temporal differences for Salmonella occurrence in various water sources. The prevalence of S. enterica in four tested ponds from farms A, B, C and D were 16, 12, 22 and 27%, respectively. While the prevalence of S. enterica in irrigation wells was significantly lower, some well water samples tested positive during the study. Salmonella Newport was found to be the predominant serovar isolated from water samples. All poultry-houses of the three tested broiler farms were Salmonella-positive at certain sampling points during the study with prevalence ranging from 14.3 to 35.4%. Salmonella was found to be able to survive up to four months in poultry litter amended soils from the tested farms in 2014, and up to six months in 2015. This research examined the dynamics of S. enterica in relationship to water source, poultry litter, and amended-soil in a major agricultural area, and provides useful information for food safety risk assessments.